Energy efficiency, productivity and profitability of rice (Oryza sativa L.) based cropping systems for selected conservation practices. Issue 14 (6th December 2017) - Rautaray, Sachin Kanta; Mishra, Atmaram; Verma, Om Prakash
ABSTRACT: A field experiment was conducted in split plot design to examine the energy efficiency, productivity, and profitability of 6 rice based cropping systems for selected conservation agricultural (SCA) and the conventional (CNV) practices during the years 2010 to 2012. Results revealed that rice crop grown in wet season with SCA resulted in higher net energy, energy output: input ratio, energy productivity, and net returns as compared to CNV. Also, in the dry season, higher yield, net return, net energy and the net economic water productivity (NEWP) were noted for the SCA. Among the dry season crops, sunflower recorded highest net energy (57.2 GJ ha −1 ) followed by horsegram and cabbage. The NEWP was highest for babycorn (US $ 0.198 m −3 ), followed by cabbage and sweetcorn. However, the per cent increase in net return, net energy and the NEWP for SCA as compared to the CNV was highest for horsegram followed by sunflower. Despite having low system productivity, rice-sunflower and rice-horsegram cropping systems were more energy efficient with high net energy of 194.4 and 169.4 GJ ha −1, respectively. These two systems were low water demanding and helped in buildup of soil organic carbon, nitrogen (N), phosphorus (P) and potassium (K).